The Evaluation of Actions Taken in the Healthcare Facility During the SARS-CoV-2 Pandemic, and Their Impact on Work Motivation: A Survey Report - Frączkiewicz-Wronka, Aldona; Ostrowska, Sabina; Woźniak-Holecka, Joanna (Journal of Public Governance, 2021)
Objectives: The global crisis, which the outbreak of the SARS-Cov-2 pandemic undoubtedly is, has forced healthcare facilities to implement a variety of sanitary procedures. These have strongly affected the staff, contributing to decreased work motivation and occasional refraining from work caused by the threat of infection. The purpose of this study was to assess the human resource management practices implemented by the managers at the Rymanow Health Resort in the first two months after the SARS-CoV-2 outbreak had been declared.Research Design & Methods: The study used the direct interview method (PAPI) and inference based on participatory observation. The respondents were medical workers employed in the health resort hospital and rehabilitation centre. 96% of the respondents participated in the PAPI survey, which is over 70% of the surveyed population. Participatory observation data was obtained from a member of the management of the healthcare facility.Findings: The respondents pointed to their increased and changed workload. Despite concerns about their own health and life, only one-third of the employees used various forms of refraining from work during the pandemic. The vast majority of the respondents positively assessed the actions taken by the employer in the first two months after the Polish government had declared the state of emergency.Implications / Recommendations: The main resource that is crucial for the success of the organisation deliveringhealthcare services is the employees, as it is them who design and utilise solutions, create organisations, and actively participate in their functioning. With regard to the employees of institutions providing healthcare services, ensuring security in work environment is paramount due to the units’ responsibility for the achievement of public interest and the administration of public funding. This is why it is so important for the employers to take action to create a friendly work environment, which is absolutely necessary for the healthcare sector to accomplish its mission.Contribution / Value Added: The results led to the formulation of the thesis that the procedures implemented bythe employer yielded measurable effects, as employees decided to stay in their workplaces despite the risks posed as a result of the coronavirus pandemic.